Art as evidence writings on art and material culture - Prown, Jules David 1930- (Yale University Press, 2001)
Art As Evidence celebrates the career of Jules Prown, historian of American art and a pioneer in the study of material culture. It brings together some of his most influential essays along with an introductory chapter, and an intellectual autobiography.
Includes bibliographical references and index
Keywords: Trumbull, John -- 1756-1843; Prown, Jules David -- 1930-; Homer, Winslow -- 1836-1910; West, Benjamin -- 1738-1820; Eakins, Thomas -- 1844-1916; Peale, Charles Willson -- 1741-1827; Copley, John Singleton -- 1738-1815; Geschichte 1700-1800; Geschichte 1800-1900; Geschichte 1780-1900; Geschichte 1700-1900; 18e siècle; Art américain; Beeldende kunsten; Culture matérielle; Kunstnijverheid; Peintre; Kunst; Art, American -- 18th century; Art, American -- 19th century; Material culture -- United States; Malerei; États-Unis; USA; Aufsatzsammlung